Social and Linguistic Adaptation among Aceh Singkil Students in Banda Aceh: Negotiating Kalak Kampong Identity - Anisya Adelia Ramadhana; Muhammad Thalal; Muhammad Yunus Ahmad (Journal of Aceh Studies, 2026)
Background: Aceh Singkil students migrating to Banda Aceh for higher education enter a highly diverse, multi-ethnic urban campus environment. As an ethnic minority, these students face significant social and linguistic pressures to adapt to the dominant cultural norms, risking the loss of their distinct “Kalak Kampong” (village resident) identity and native language. Objective: This study investigates how Aceh Singkil diaspora students negotiate and maintain their Kalak Kampong cultural identity while dealing with these adaptation pressures in Banda Aceh. Methodology: Using a qualitative descriptive approach, primary data was collected through in-depth interviews with 10 Aceh Singkil students enrolled in various universities. The transcripts were analyzed utilizing the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion verification. Key Findings: The findings reveal that students actively employ strategic code-switching and bicultural integration. They utilize the Indonesian language and modify their social behavior for interethnic communication to ensure academic and social integration. Simultaneously, they strictly preserve the Singkil language and core communal values during intra-group interactions to maintain hometown solidarity. Furthermore, students maintained strong cultural pride and benefited from a welcoming campus environment that fostered curiosity rather than prejudice. Implications: The study demonstrates that internal provincial student mobility does not inherently erase minority identities. The practical implications highlight the need for university administrators to design inclusive campus policies and revitalize formal regional student organizations to actively support cultural diversity and bicultural resilience in modern educational hubs.